Dreams and Drama of Applied Image Forensics - Rieß, Christian (IH MMSec 2024 - Proceedings of the 2024 ACM Workshop on Information Hiding and Multimedia Security, 2024)
Image forensics aims to provide computational tools for determining origin and authenticity of an image or for reconstructing the processing history of an image. In a broader definition, image forensics also includes the reconstruction of quantities of interest with the help of specific information within an image, for example the height of a person that is shown in the image.
CRIS-Team Scopus Importer:2024-07-12
Keywords: explainability; image forensics; maintainability; robustness; sensitivity and specificity